Effects of heat treatment on the corrosion behavior and mechanical properties of aluminum alloy 2024 - Fatima Ezzohra El Garchani; Hassane Lgaz; Savaş Kaya; Han-Seung Lee; Sobhy M. Ibrahim; Maryam Chafiq; Young Gun Ko; Moulay Rachid Kabiri (Journal of Materials Research and Technology, 2023)
Aluminum alloy, specifically 2024, is extensively utilized in the automotive and aerospace industries due to its light weight and superior mechanical properties. This study explores the corrosion behavior and mechanical characteristics of this alloy following quenching and aging heat treatments. Accelerated corrosion tests involved immersing samples in a salt spray chamber with a 5% NaCl solution, maintained at a temperature of 40 °C with a neutral pH. The alloy's microstructure and corrosion behavior were examined before and after the corrosion test, which included a heat treatment at 495 °C and aging for five days. Multiple tests, such as Vickers microhardness, optical microscopy, scanning electron microscopy (SEM), and tensile tests were performed. The surface characteristics, specifically the refined microstructure and residual stresses, were analyzed and their impact on localized corrosion was evaluated. The maximum strength value rose from 411 MPa to 512 MPa, and elongation increased correspondingly. Concerning corrosion sensitivity, a reduction was observed in the following order: AA2024-T3 (natural condition), AA2024-T3 (tempered condition), and AA2024-T3 (aged condition). The aged treatment appeared to enhance corrosion resistance, potentially due to the minimized size of corrosion products observed post-etching in various regions.